Giving Victims a Voice in Parole Hearings: South Australia's Experience. Issue 1 (July 2018) - O'Connell, Michael; Fletcher, Sarah
Much of the limited research on parole has focused on the prisoner perspective. There is a paucity of research on the victim perspective. This article draws on quantitative and qualitative information attained during semi-structured interviews of co-victims of murders that were conducted by the Commissioner for Victims' Rights, South Australia. This information offers an insight into co-victims' views on whether murderers should be released on parole; co-victims' safety concerns should murderers be released; and, co-victims' views on the parole process. The results confirm the importance of victim participation in the parole process.